PENERAPAN TEKNOLOGI AUGMENTED REALITY SEBAGAI MEDIA PROMOSI PRODUK FURNITURE ALUMINIUM - Mohamad Rizki Laiya; Muhammad Rifai Katili; Ahmad Azhar Kadim (Diffusion: Journal of Systems and Information Technology, 2023)
Promotional media using augmented reality technology is becoming popular as it can make customers interesed in what is being offered of promoted. Mega Aluminium 77 store is a furniture business engaged in mental materials. However, Mega Aluminium 77 store has no promotional media that explains the product interactively and in detail. Thus, the present study aimed to develop promotional media for Mega Aluminium 77 store based on augmented reality technology using Engine Unity. Additionaly, this study employed Multimedia Development Life Cycle (MDLC), which has six stages: concept, design, material collecting, assembly, testing, and distribution. The finding of the study obtained was in the form of Android-based augmented reality apps that can display a 3 (three) dimensional visualization of the product to be promoted, as well as can display detailed information in the form of prices and sizes that have been adjusted to the existing product on Mega Aluminium 77 store.